1985
DOI: 10.1007/bf00583600
|View full text |Cite
|
Sign up to set email alerts
|

Segmental differences in electrical properties and Na-transport of rabbit caecum, proximal and distal colon in vitro

Abstract: Electrical potential difference, short circuit current, tissue conductance, and unidirectional Na-fluxes were measured in four segments of the rabbit large intestine in vitro. Compared to the relatively tight, low conductance distal colon, caecum and proximal parts of the colon are leaky epithelia with high conductances. Net Na-absorption was highest in caecum, and then decreased gradually towards the distal colon, whereas potential and short circuit current where high in the caecum and proximal colon, low in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 18 publications
2
23
1
Order By: Relevance
“…Baseline I SC in DC 4 was significantly higher than that observed in DC 1 , although the transepithelial resistance has no significant difference between DC 1 and DC 4 which was consistent with the results of previous reports. 12,13) It has been reported that a spontaneous production of neuronally acting prostaglandins in rat distal colon. 6) Park et al found that suppression of prostaglandin biosynthesis decreased the secretory responses to the CCh and forskolin in human rectum and increased the sensitivity of the tissues to CCh and forskolin in human ascending colon, and they considered that the clear segmental heterogeneity with regard to electrogenic secretion between ascending colon and rectum can be explained by differences in the action of endogenous prostaglandin.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline I SC in DC 4 was significantly higher than that observed in DC 1 , although the transepithelial resistance has no significant difference between DC 1 and DC 4 which was consistent with the results of previous reports. 12,13) It has been reported that a spontaneous production of neuronally acting prostaglandins in rat distal colon. 6) Park et al found that suppression of prostaglandin biosynthesis decreased the secretory responses to the CCh and forskolin in human rectum and increased the sensitivity of the tissues to CCh and forskolin in human ascending colon, and they considered that the clear segmental heterogeneity with regard to electrogenic secretion between ascending colon and rectum can be explained by differences in the action of endogenous prostaglandin.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have suggested that the Received for publication 11 February 1987 and in revised form 26 October 1987. cecum absorbs Na efficiently (4,6). In the present study, we characterize in detail the ion transport characteristics of rabbit cecum in vitro.…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies from our laboratory and others have established that there are important differences between the proximal and distal colon (1)(2)(3)(4). Additionally, there now appear to be differences within the rabbit proximal colon between the segment immediately distal to the cecum (the triple haustrated segment) and the region 10 cm beyond the cecum (the single haustrated segment) (4,5).…”
Section: Introductionmentioning
confidence: 92%
“…In proximal colon, ileum, and jejunum, the major increase in sodium absorption and short-circuit current produced by glucocorticoids is amiloride resistant, a finding uncharacteristic for an aldosterone-induced response (2,8,36,49). In distal colon, amiloride-resistant transport may be induced with low doses or concentrations ofdexamethasone and amiloride-inhibitable transport induced at doses ofdexamethasone greater than the 10 nmol dose used in this study (2,3,5,7,8,17,18).…”
Section: Discussionmentioning
confidence: 71%
“…The proximal colon of intact rats is characterized by a low transmural PD, -3.4±0.2 mV (Fig. 1), which may not be generated by active sodium absorption (15,19,31,(34)(35)(36). However, it does decrease significantly with adrenalectomy.…”
Section: Resultsmentioning
confidence: 99%